Use of artificial intelligence in editing local online media - Ničić, Aleksandra (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
Artificial intelligence (AI) has begun to change not only the habitus of journalists, but also the editorial practices themselves. Faced with a lack of resources, local editors are trying to use the capacities provided by artificial intelligence, side by side, with colleagues from large media. However, financial vulnerability, lack of time for training and lack of staff stand as obstacles to the effective application of artificial intelligence in local online media editing.Therefore, the main goal of this paper is to investigate to what extent and in which ways are the AI tools used in editing local online media in Serbia, as well as the specific challenges that local editors face in this domain. The research is focused exclusively on the application of AI tools in editorial processes, and its core are the experiences, decisions, attitudes, dilemmas and predictions of local online media editors regarding the use of artificial intelligence in online media editing. Key methods were an in-depth interview and a survey, in which participated the editors of the local online media 021.rs, In medija, Za medija, Kolubarske, Al pres, Glas Šumadije and Glas Podrinja.The research results showed that the editors of local online media most often apply artificial intelligence tools for copy editing and predictive analytics. As the biggest problem they emphasize insufficiently developed skills for applying AI tools and the lack of clear ethical rules in this domain. Thus, only two local newsrooms that are part of the research have guidelines for the ethical use of artificial intelligence, while others are still planning to develop internal codes for this purpose.
Keywords: artificial intelligence; online journalism; local media; online media editing; generative artificial intelligence tools; non-generative artificial intelligence tools